Improving the Bearing Capacity of Clay Soil Using Plastic Bottle Waste (Journal of Engineering, 2024)
With the increase in industry and industrial products, quantities of waste have increased worldwide, especially plastic waste, as plastic pollution is considered one of the wastes of the modern era that threatens the environment and living organisms. On this basis, a solution must be found to use this waste and recycle it safely so that it does not threaten the environment. Therefore, this research used plastic waste as an improvement material for clay soil. In this research, two types of tests were conducted, the first of which was a laboratory test, where the undrained shear strength (cohesion), compression index (Cc), and swelling index (Cr) of the improved and unimproved soils were calculated (plastic was added in proportions (0.5, 1, 1.5, 2)%. The second part of the examination was done through physical modeling, where 2% of plastic was used, considered the optimal percentage in this research, and the calculation of the carrying capacity-settlement relationship for both the improved and unimproved soils. Using this percentage of plastic showed an improvement in the relationship between the bearing capacities of soil vs. subsidence, as an increase in the amount of stress was observed from 405 KPa to 459 kPa at 10% of subsidence.